Evaluation of Replication Protein A (RPA) as a prognostic and therapeutic target in breast and ovarian cancer - Algethami, Mashael (2024)
Introduction: Replication protein A is a heterotrimeric complex composed of three linked subunits encoded by unique genes: RPA1 (chromosome 17p13, 70 kDa), RPA2 (chromosome 1p36.11, 32 kDa), and RPA3 (chromosome 7p13.3, 14 kDa). RPA is a critical ssDNA binding protein that coats and protects exposed ssDNA from endogenous nucleases during repair. RPA is essential for DNA replication, repair, and recombination.